Inside Back Cover: Additive‐Free Transparent Triarylamine‐Based Polymeric Hole‐Transport Materials for Stable Perovskite Solar Cells (ChemSusChem 18/2016). Issue 18 (15th September 2016) - Matsui, Taisuke; Petrikyte, Ieva; Malinauskas, Tadas; Domanski, Konrad; Daskeviciene, Maryte; Steponaitis, Matas; Gratia, Paul; Tress, Wolfgang; Correa‐Baena, Juan‐Pablo; Abate, Antonio; Hagfeldt, Anders; Grätzel, Michael; et al.
Abstract : The Inside Back Cover picture shows a perovskite solar cell in a multilayer architecture containing a fluorine‐doped tin oxide substrate, mesoporous TiO2 and triple‐cation perovskite active layer, new dopant/additive‐free triarylamine polymeric hole‐transport material, and gold electrode. Despite the absence of dopants/additives, the use of this new hole‐transport material (pink layer) yields highly efficient perovskite solar cells enabling stable devices even at elevated temperatures (85°C). More details can be found in the Communication by Matsui et al. onpage 2567 in Issue 18, 2016 (DOI:10.1002/cssc.201600762 ).